2018
DOI: 10.1038/s41598-018-21094-6
|View full text |Cite
|
Sign up to set email alerts
|

Importance of embryo aneuploidy screening in preimplantation genetic diagnosis for monogenic diseases using the karyomap gene chip

Abstract: We investigated the incidence of aneuploidy in embryos from couples carrying monogenic diseases and the effect of embryo aneuploidy screening on the monogenic disease preimplantation genetic diagnosis (PGD). From November 2014 to April 2017, 36 couples carrying monogenic diseases were enrolled. The karyomap gene chip technique was used to analyze the blastocysts from the subjects and select normal embryos for transfer. A total of 43 single-gene PGD cycles were performed. A total of 687 eggs were obtained and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…One publication reported mosaicism on a per chromosome level only . The remaining five publications reported on mosaicism ranging from 0% (0/175 and 0/18 embryos) to 10.8% (11/102 embryos), with the two largest studies reporting 3.7 (42/1122 embryos) and 6.8% (44/646) . Three of the six studies detail their classification and transfer policy with respect to mosaic embryos, with two never transferring mosaic embryos, and one considering mosaic embryos for transfer if there were no euploid embryos available and the level of mosaicism was 40% or less .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the patient population (53.2%) had at least one blastocyst with unaffected single gene defect were aneuploid, approximately 26.5% of normal or nonpathogenic blastocysts diagnosed based on monogenic disease PGD were aneuploid which would have been transferred, resulting in negative impacts in pregnancy outcome unless PGS had performed. 40 Conversely, concurrent screening demonstrably aided in embryo selection, as evidenced by the significant improvement in single embryo transfer rates, so 24-chromosome aneuploidies screening became more and more popular to apply in embryos biopsied for PGD to reduce the risk of miscarriage in the gestational period. [41][42][43] Indeed, PGD combined with PGS allowed opting for an embryo that did not carry the mutated allele and euploid embryos to transfer into the mother's uterus then, fortunately, achieved pregnancy with a baby girl.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of high-throughput genotyping and sequencing technology, the massive single nucleotide polymorphisms (SNPs) were extensively identified in different species, which usually used for high-density map construction, genome-wide association analysis, gene mapping, gene chip, MAS, etc. (Wang et al, 1998;Slate et al, 2009;Huang et al, 2010;Shao et al, 2015;Li et al, 2018). However, whole genome deep re-sequencing is still costly and not necessary for most studies.…”
Section: Introductionmentioning
confidence: 99%